Siskeudes: Membangun Akuntabilitas Keuangan Desa dalam perspektif New Public Governance: Bahasa Indonesia - Suwuh, Adrian Hendrik William; Wardiyanto, Bintoro (Universitas Nahdlatul Ulama Blitar, 2025)
This study looks at the implementation of the Village Financial System (SISKEUDES), developed by the Financial and Development Supervisory Agency (BPKP), as a strategic step in efforts to foster accountability and transparency of village finances in the perspective of New Public Governance (NPG). SISKEUDES assists village governments in financial management from planning to reporting. Even though this system has helped improve village financial governance, there are still some issues that need to be addressed. These include limited access to technology, lack of digital knowledge, and low community participation. In the context of NPG, active community participation and collaboration with various responsible parties are considered essential to create inclusive, transparent, and accountable public governance. This research uses a qualitative approach based on library research. The results show that the implementation of SISKEUDES should be supported by increased capacity of village officials, wider access to technology, and more active community participation in sustainable village development.